Immunomodulatory properties of IgG glycosylation and the anti-inflammatory mechanism of intravenous immunoglobulin - Yu, X (2013)
The IgG Fc domain mediates a range of antibody effector functions, including antibody dependent cell-mediated cytotoxicity (ADCC), complement activation, phagocytosis, and the recently emerged general anti-inflammatory effect of immunoglobulin therapy (IVIg). The conserved N-glycan attached to Fc N297 maintains the Fc structural integrity for the effector functions, while its glycoform is known to modulate the affinity for the Fc γ-receptors (FcγRs), complement, and the C-type lectin DC-SIGN. IgG Fc exhibits protein-directed glycosylation characterized by a series of biantennary complex type glycoforms, with a small population of sialylated species. The sialylated Fc has been proposed to bind DC-SIGN and initiate an anti-inflammatory signalling pathway. The restricted Fc glycan processing is partially attributed to the hydrophobic interaction between Fc glycan and the hydrophobic Fc protein backbone. Mutations within the hydrophobic Fc protein-glycan interface dramatically increases Fc glycan processing, while concomitantly decreases Fc affinity for the FcγRs. However, it is unclear whether this disrupted Fc-FcγR interaction was due to the increased terminal glycan processing, or the perturbed Fc protein-glycan interface. Here, the integrity of the Fc protein-glycan interface was demonstrated to be important in maintaining the productive Fc-FcγR interaction independently of glycoform. This glycoform-independent effect was exploited to generate novel inhibitory Fc variants. In addition, the interaction between sialylated IgG and the putative IVIg receptor DC-SIGN was re-evaluated. Analysis shows that IVIg binds DC-SIGN in a glycan-independent, Fab-mediated manner. Furthermore, the effect of IVIg sialylation on human antigen presenting cells was examined; evidence presented here indicate that IVIg deglycosylation, not desialylation, has an anti-inflammatory effect on human dendritic cells (DCs). These data suggest the need for a general re-evaluation of the current mechanistic model of anti-inflammatory IVIg.